ANALYSIS OF THE DIVERSITY OF RICE FARMING HOUSEHOLD BUSINESSES LEBAK RICE FIELDS ON THE OUTSKIRTS OF PALEMBANG CITY - Sari, Komala; Kurniawan, M. Ardi (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2024)
Livelihood strategies are various alternative efforts carried out by households to fulfill living needs for sustainable livelihoods. Through the livelihoods approach, we can understand how people/communities create a livelihood, and how they try to survive. The lives of lowland rice farmers on the outskirts of Palembang City are inseparable from the problem of the water regime conditions of the lowlands with all the impacts it causes as well as social and economic aspects and resource aspects (land conversion) from agriculture to residential and housing land. This research aims to 1) analyze the level of business diversity of farmer households, 2) calculate the amount of income of lowland rice farmer households from the on farm, off farm and non farm sectors. 3) distribute the contribution of various incomes from the off-farm and non-farm sectors to the household income of lowland rice farmers on the outskirts of Palembang City. The data used and the analysis carried out used a combination of primary survey data and qualitative data from the results of in-depth interviews with a sample of 32 families. The results of the research show that the diversity of household businesses of lebak farmers on the outskirts of Palembang City, with the calculation of the entropy index, obtained a value of 0.73. This shows that the efforts made by household members are very good. diverse. The average income from rice farming is Rp. 16,168,113.32 /lg/yr and its contribution to the household is moderate (54.96%), the average non-rice farming income is Rp. 4,319,548.42/year with its contribution to households in the low criteria category (14.68%), and the average non-farming income is IDR. 8,928,750.00/year and its contribution to households in the medium criteria category (30.35%).